Metropolis [large type] - Kerr, Philip (Kerr, Philip. Bernie Gunther novel., 2019)
A portrait of Bernie Gunther in his twenties: He's young, but he's seen four bloody years of trench warfare. And he's not stupid. So when he receives a promotion and a ticket out of Vice squad, he knows he's not really leaving behind the criminal gangs, the perverse sex clubs, and the laundry list of human corruption. It's 1928 and Berlin is a city on the edge of chaos, where nothing is truly verboten. But soon a new wave of shockingly violent murders sweeps up society's most vulnerable, prostitutes and wounded ex-soldiers begging on the streets.